TEKNOLOGI PENGEMBANGAN USAHA TERNAK AYAM KAMPUNG BERBASIS PENDIDIKAN PONDOK PESANTREN DI KOTA JAYAPURA - Suharno, Suharno; Tanjung, Rosye HR.; Komari, Komari; Sufaati , Supeni; Maulani, Sherlita; Ruhani, Annisa A. (JURNAL PENGABDIAN PAPUA, 2023)
More Chicken is one of the important sources of protein in fulfilling food in the world, so the need for chicken meat in the market is always high. The need for native chicken meat and eggs can be increased through chicken farming. The purpose of this activity is to design and introduce chicken farming technology based on Islamic boarding school education in Jayapura City. The method used is intensive counselling through Forum Group Discussion (FGD), and guidance on the practice of making and planning the development of native chicken farms. The results of the activity showed that the location of Papua Madani Boarding School (PMBS) was qualified for the development of native chicken farms. Adequate area and human resources according to competence are very appropriate for this activity. Most participants (96.25%) can understand how to raise native chickens, although a small percentage (0.83%) do not fully understand the method of chicken rearing. In general, this activity was able to increase the knowledge of the students by 37.5% (from 70.0% to 96.25%) related to the native chicken farming system. This knowledge capital is expected to be the basis for the development of native chicken farms in Islamic boarding schools.  Keywords: chicken; agroindustry; boarding school